Predictive value of uterine artery pulsatility index for cesarean delivery in late-onset fetal growth restriction - Golgelioglu, Melisa; Akverdi, Gulcan; Akcabay, Cigdem; Kavak, Ebru Celik; Kavak, Salih Burcin (Elsevier, 2026)
Objective: This study aimed to evaluate the predictive value of uterine artery pulsatility index (PI) for cesarean delivery in pregnancies complicated by late-onset fetal growth restriction (FGR) undergoing induction of labour. Methods: This retrospective cohort included singleton pregnancies with late-onset fetal growth restriction (>= 32 weeks) that underwent labour induction at a tertiary center. Women were categorized according to mode of delivery as vaginal delivery (n = 46) or cesarean delivery (n = 43). Uterine artery PI, abnormal uterine artery PI (>95th percentile), umbilical artery PI, middle cerebral artery PI, middle cerebral artery peak systolic velocity, and cerebroplacental ratio were evaluated. Multivariate logistic regression and receiver operating characteristic (ROC) analyses were performed. Results: Among 89 women with late-onset FGR undergoing labour induction, 46 had vaginal delivery and 43 underwent cesarean delivery. Maternal characteristics and Bishop score were similar between groups. The mean uterine artery PI was higher in the cesarean group (1.03 +/- 0.24 vs. 0.82 +/- 0.25, p < 0.001), and abnormal uterine artery PI (>95th percentile) was more frequent (69.8% vs. 26.1%, p < 0.001). Cesarean delivery was most commonly performed for intrapartum fetal distress (69.8%), and uterine artery PI was significantly higher in these cases compared with failed induction (p = 0.02). Lower estimated fetal weight and higher uterine artery PI independently predicted cesarean delivery. Uterine artery PI demonstrated good discriminatory ability (AUC 0.81; cutoff 0.97). Conclusions: In late-onset FGR pregnancies undergoing labour induction, an elevated uterine artery PI was associated with cesarean delivery and may serve as a risk stratification tool to support individualized intrapartum management.
Keywords: Doppler ultrasonography; Neonatal morbidity; Obstetric complications; Placental insufficiency; Uterine artery resistance